Playful Study Design untuk Meningkatkan Keterlibatan Belajar dan Berpikir Kritis Siswa SMA - Yunida Octavia Azzahra; Rizki Hikmawan (Cetta: Jurnal Ilmu Pendidikan, 2026)
Student engagement and critical thinking are essential competencies in 21st-century education, yet many high school learning activities remain teacher-centered and provide limited opportunities for active participation. Playful Study Design (PSD), which integrates enjoyable and competitive learning experiences, has the potential to enhance students' involvement and higher-order thinking. This study aimed to examine changes in Student engagement and critical thinking skills following the implementation of PSD in Informatics learning among eleventh-grade high school students. A quantitative approach employing a one-group pretest-posttest   design was used with 34 students of class XI CI at SMAN 1 Purwadadi. The intervention integrated designing fun and designing competition into collaborative problem-solving, discussions, presentations, and reflective learning activities. Data were collected using a student engagement questionnaire and an essay-based critical thinking test. Data were analyzed through validity, reliability, normality, and Paired Sample t-tests. The findings revealed statistically significant improvements in both Student engagement and critical thinking skills after the implementation of PSD (p < 0.001). Students demonstrated higher participation, stronger collaboration, and improved analytical performance in the posttest  compared with the pretest. These findings indicate that PSD was associated with positive changes in Student engagement and critical thinking skills. However, because the study employed a one-group pretest-posttest   design without a control group, the results should be interpreted cautiously and cannot be considered conclusive evidence of causal effectiveness. This study highlights the potential of PSD as a student-centered learning approach that supports the development of competencies required for 21st-century education.